1993
DOI: 10.1111/j.1468-5957.1993.tb00269.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Small Business Accounting Bases and Accountant Service Levels on Loan Officer Decisions

Abstract: This study examines effects of four combinations of accounting bases and service levels — GAAP and income tax bases, and audit and review service levels — on loan officers' decisions, both separately and in interaction. It examines effects on loan decisions and perceptions of interest rates, default risk, confidence, and usefulness. The interaction of accounting basis and service level significantly affects perceived confidence but does not affect other decisions. Accounting basis and service level separately … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Much of the accounting literature assumes that accrual accounting is more informative than cash accounting, and surveys find that small business lenders rate accrual accounting their preferred source of financial information for decision-making (Baker and Cunningham, 1993;AICPA, 2004).…”
Section: Accounting-based Lendingmentioning
confidence: 99%
“…Much of the accounting literature assumes that accrual accounting is more informative than cash accounting, and surveys find that small business lenders rate accrual accounting their preferred source of financial information for decision-making (Baker and Cunningham, 1993;AICPA, 2004).…”
Section: Accounting-based Lendingmentioning
confidence: 99%
“…This information can be prepared using cash or accrual accounting. 4 Much of the accounting literature assumes that accrual accounting is more informative than cash accounting, and surveys find that small business lenders rate accrual accounting their preferred source of financial information for decision-making (Baker and Cunningham, 1993;AICPA, 2004).…”
Section: Accounting-based Lendingmentioning
confidence: 99%
“…To measure similar economic events in inconsistent ways, depending on the nature of the company and its financial statement users, would create confusion (Kelley, 1976;Stanga and Tiller, 1983) and have a detrimental impact on comparability (Nair and Rittenberg, 1983). It should also be noted that lenders, a primary user of private company financial statements, have often expressed support for requiring one set of GAAP for all businesses regardless of size or type (e.g., see Abdel-Khalik, Collins, Shields, Snowball, Stephens, and Wragge, 1983;Robert Morris & Associates, 1985;Baker and Cunningham, 1993;and AcSB, 2007).…”
Section: Background and Prior Researchmentioning
confidence: 99%
“…A third area of research has looked at the effect of differing accounting standards on decision making or decision processes of financial statement users. It has been found that earnings per share, deferred income tax, and inflation-adjusted information do not appear to be used in small business lending decisions, but that capitalized lease information is used (Campbell, 1984); use of the cost versus equity reporting of investee companies affects lending decisions (Wilkins and Zimmer, 1985); use of tax-basis accounting rather than GAAP affects perceptions of risk, usefulness of the report, confidence in the financial report, and the need for additional information (Coker and Hayes, 1992;Baker and Cunningham, 1993); and prospective versus retroactive implementation of the postretirement benefits standard by small businesses affected loan officers' loan decisions (Ivancevich, Ivancevich, Cocco, and Hermanson, 1997).…”
Section: Background and Prior Researchmentioning
confidence: 99%